Quality of resection margin with patient specific instrument for bone tumor resection - Robin Evrard; Thomas Schubert; Laurent Paul; Pierre-Louis Docquier (Journal of Bone Oncology, 2022)
Background: Patient Specific Instruments (PSI) is currently a proven technique for bone tumor resection. In a previous publication, we analyzed the quality of margin resection of pelvic sarcoma resections with the use of PSI (by pathologic evaluation of the margins). In this new study, we compare preoperative resection planning and actual resection margins by MRI analysis of the resection specimens. Methods: Between 2011 and 2020, 31 patients underwent bone tumor resection with the use of PSI. Preoperatively, the margins were planned with a software and PSI were made according to these margins. Postoperatively, the surgical resection specimens were analyzed with MRI. Resection margins were measured with the same software used in the preoperative planning. Results: All margins were safe (free of tumor). The differences between preoperative planned margins and the obtained ones were within the range −5 to +5 mm. The correlation between planned margin and the obtained one was excellent (R2 = 0.841; p < 0.0001). Conclusions: This study demonstrates the accuracy of PSI. In our series, all resection margins were safe. A minimal 5 mm-margin has to be planned but a larger sample is needed to give recommendations.